If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4 = 3(2x + -1) + -1 Reorder the terms: 4 + 5x = 3(2x + -1) + -1 Reorder the terms: 4 + 5x = 3(-1 + 2x) + -1 4 + 5x = (-1 * 3 + 2x * 3) + -1 4 + 5x = (-3 + 6x) + -1 Reorder the terms: 4 + 5x = -3 + -1 + 6x Combine like terms: -3 + -1 = -4 4 + 5x = -4 + 6x Solving 4 + 5x = -4 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4 + 5x + -6x = -4 + 6x + -6x Combine like terms: 5x + -6x = -1x 4 + -1x = -4 + 6x + -6x Combine like terms: 6x + -6x = 0 4 + -1x = -4 + 0 4 + -1x = -4 Add '-4' to each side of the equation. 4 + -4 + -1x = -4 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = -4 + -4 -1x = -4 + -4 Combine like terms: -4 + -4 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8
| q^2+5q-36=0 | | 13x^3-26x= | | -4n-34=5(-6-n) | | a^4b^2-a^2b= | | 7x-23=4x+34 | | H(t)=-16t^2+1000t+5 | | 25n+25=14n^2 | | 9+6x=25-2x | | (x+6)(3x-2)= | | 3a+24b= | | -52+6x=56-3x | | H(t)=-16t^2+0t+790 | | 3-12a+15c= | | -6(x+4)=-22-4x | | -17-6x=5-7x | | 5-2(x+2)=x-14 | | 14x-18y= | | 4x-2a=6b | | 9x+3=8x+11 | | x-4=1+2x | | N+0.5=6.4 | | y=-5x^6 | | -20+9x=x | | 316=-6(1-8x)-2x | | -133-2x=67-10x | | 61x+1=62x-1 | | 1/6t^2-25=0 | | 13-5x=7-6x | | 28=4(x-8) | | 16+6x=8x-2 | | -6n(4n-1)=0 | | x^2-10+21x=0 |